42 Factors influencing total ischaemic time in stemi. (October 2018) - Fitzgerald, G; Ibrahim, A; Coffey, J; Saunders, J; Cahill, C; Satti, Z; Ullah, I; Kiernan, T
Abstract : Introduction: Acute coronary syndrome is a major cause of morbidity and mortality in the developed world. Timely intervention in ST elevation myocardial infarction is one of the major success stories of interventional cardiology. Delays in reperfusion negatively influence 1 year mortality, and prompt recognition of symptoms and activation of the emergency response is critical. Traditional treatment targets include a 'door to balloon time' of 90 min or less, with updated guidelines of a 90 min target from ECG to vessel opening cited in the most recent ESC guidelines. This is only one component of ischaemic time however, and delay from symptom onset to call for help as well as delays in recognizing the symptoms of acute coronary syndrome and subsequent ECG can add significantly to the ischemic time and potentially impact on adverse outcomes. Potential delays pre hospital can lead to larger infarct size and subsequent complications leading to poorer outcomes. Methods: Prospective data was collected on 99 patients who presented to our service with acute STEMI between October and March 2017 in order to analyse the performance of the service and highlight potential areas for improvement. The patient demographics were analysed and total ischaemic time calculated based on the time from symptom onset to wire crossing of the lesion. Pre hospital metrics were also recorded and potential sources of delay highlighted. Data was then pooled and analysed with SPSS to give examine baseline characteristics of the patient group (table 1). Results and conclusions: A total of 99 patients were included in the study. The mean total ischaemic time was 425 min (51–3009). Mean symptoms to first call for help was 211 min (0–2550) and mean first call for help to first medical contact 18 min (0–270). The mean first medical contact to ECG time 56 min (1–1440) and the mean ECG to wire cross time was 108 min (19–624) and the mean PCI centre to wire cross time was 64 min (5–756).The results are sumarised in table 2. The data demonstrates that there is still a considerable total ischaemic time for patients with acute STEMI, and whilst door to revascularization metrics are readily emphasized in healthcare centres, better education of the public regarding symptoms of STEMI and emphasizing the importance of rapid appropriate ECGs by paramedics are important factors to consider. Implications: The traditional metric of door to revascularisation time remains an essential element of primary PCI. However the importance of patient education in recognizing potential acute coronary syndromes is an important consideration to reduce overall ischaemic time in STEMI. Whilst our ECG to wire cross time of 108 min was just slightly above target, there was a large delay in symptom onset to first call to help. This is likely a combination of varying severity of symptoms and a broad patient cohort with different thresholds for seeking medical assistance. Our study emphasizes the importance of improving total ischaemic time not just within hospital but in educating the public regarding prompt activation of the emergency response team if they have symptoms of acute coronary syndrome.